2013
DOI: 10.1074/jbc.m112.414177
|View full text |Cite
|
Sign up to set email alerts
|

The Stress Protein BAG3 Stabilizes Mcl-1 Protein and Promotes Survival of Cancer Cells and Resistance to Antagonist ABT-737

Abstract: Background:Mcl-1 inhibits apoptosis and promotes survival of cancer cells. Results: The Hsp70 co-chaperone, BAG3, prevents Mcl-1 degradation by the proteasome. Conclusion: BAG3 sustains Mcl-1 expression in cancer cells, promoting its antiapoptotic activity. Significance: Mcl-1 expression is a major determinant of resistance in human cancer, so BAG3 is a potential target for anticancer drug discovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 66 publications
3
56
0
Order By: Relevance
“…We found that ABT737 alone or in combination with paclitaxel had little effect on ES2 cell viability (Fig. 4B), which is consistent with earlier reports showing that Mcl-1 mediates ABT737 resistance (11,22,29,30).…”
Section: Mcl-1-specific High-affinity Antagonist Mim1 Increases Sensisupporting
confidence: 82%
See 1 more Smart Citation
“…We found that ABT737 alone or in combination with paclitaxel had little effect on ES2 cell viability (Fig. 4B), which is consistent with earlier reports showing that Mcl-1 mediates ABT737 resistance (11,22,29,30).…”
Section: Mcl-1-specific High-affinity Antagonist Mim1 Increases Sensisupporting
confidence: 82%
“…In addition to the BAG domain, BAG3 contains a WW domain near its N-terminus and a proline-rich region (multiple PXXP motifs) (16,17), and our earlier study showed that BAG3 also regulates cell motility and tumor growth, invasion and metastasis (18). Moreover, several lines of evidence indicate that downregulation of BAG3 enhances chemotherapy-mediated apoptosis among cancer cells (19)(20)(21), which is consistent with the recent finding that BAG3 stabilizes Mcl-1, Bcl-2 and Bcl-X L , thereby promoting cancer cell survival (22,23). The precise mechanism by which BAG3 exerts these effects remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can be simply speculated that, with deficiency of BIS, BAG1 may replace BIS in the formation of complex with HSP70 and facilitate the proteasome-dependent degradation of SOD, resulting in impaired induction of SOD1 or SOD2 expression. Supporting this idea, BIS has been recently reported to stabilise myeloid cell leukaemia sequence 1 (BCL2-related) (MCL-1), preventing its HSP70-dependent degradation [40]. However, the constitutive expression of SOD1, as well as SOD2, was higher in BIS-HT mice than in BIS-WT mice before induction of diabetes, which correlates with basal SOD activity.…”
Section: Discussionmentioning
confidence: 74%
“…However, ABT-263 and ABT-737 are unable to bind Mcl-1. Therefore, Mcl-1 is not inhibited by ABT-263 or ABT-737 and is considered to be a major factor in resistance to ABT-737 (15,41,42). Furthermore, the amplification of the Mcl-1 locus is the most frequent somatic genetic event in human cancer (18).…”
Section: Discussionmentioning
confidence: 99%